Silver Nanorods Layer Based on Polyvinyl Alcohol on Glass Substrates by Dip-Coating Method - Junaidi Junaidi; Agus Riyanto; Kuwat Triyana; Khairurrijal Khairurrijal (Universitas Negeri Surabaya, 2019)
This research reports the investigation of the performance of a thin layer based on silver nanorods using the dip-coating method. The synthesis was conducted by polyol method at an oil bath temperature of 140 °C. In the synthesis of silver nanorods, materials used were silver nitrate (AgNO3) as the main raw material, ethylene glycol (EG) as the solvent, and a small amount of sodium chloride (NaCl) as a mediated-agent (precursor). Polyvinyl alcohol (PVA) used as a capping agent and stabilizer in this process. Diameter and length of silver nanorods were 800 nm and 15 µm, respectively. Furthermore, the silver nanorods suspension was deposition onto a glass substrate with a variety of dipping cycles. The result showed the thickness of the thin layer is linear with a number of dipping cycles. Electrical and optical properties of thin layer show that sheet resistance about of 30 Î© sq-1 by transmittance above of 80%. The silver nanorods thin film can be used as a conductive and transparent electrode for various optoelectronic applications.